On Dependency between Wishes and Perception - A. I. Ponomarev; K. G. Frolov (Дискурс, 2021)
Introduction. Empirical studies of recent years convincingly show that the character of sensory perception can be influenced by non-cognitive mental states of the agent, such as her desires. The aim of the paper is to analyze how this causal connection between agent's wishes and her sensations can affect the epistemological status of dependent sensations.Methodology and sources. The author examines S. Siegel's argument on this issue. S. Siegel argues that the empirically proven dependence of sensations on desires (wishful seeing) should lead to a decrease of the epistemological status of sensations to the same extent as the dependence of beliefs on desires (wishful thinking) leads to a decrease of the epistemological status of these beliefs. Thus Siegel's argument concludes that the phenomenon of wishful seeing deprives us of any reason to accept sensations as credible evidence of the states of the world. So, this is an argument in favor of skepticism.Results and discussion. The article discusses two main strategies for rejecting Siegel's argument. According to the first strategy proposed by R. Long, sensations are not so similar to beliefs that one can conclude that their epistemological status should be decreased on the basis of their dependence on desires. According to another strategy for refuting Siegel's argument, proposed by A. Raftopoulos, the influence of desires on perception does not extend to early vision. Early vision is free from the influence of higher order conscious mental states. The dependence of the results of sensory perception on other mental states is reduced to the influence of these states on the agent's attention. At the same time, attention can be volitionally controlled and can be trained. Therefore dependent perception under certain conditions can be rationally accepted.Conclusion. Thus, the article shows that, even though perception is dependent on other non-cognitive mental states, such as desires, this dependence does not necessarily lead to a decrease in the epistemological status of sensations, so sensations can be rationally accepted under certain conditions. This means that Siegel's argument for skepticism is not compelling.